IMovie '09 & iDVD '09 for dummies - Cohen, Dennis R. (Wiley, 2009)
"IMovie and iDVD are preloaded on every new Mac. Especially if you're new to the Mac, you'll appreciate how iMovie '09 & iDVD '09 For Dummies walks you through every step, starting with transferring footage from your camcorder to your computer. You'll learn to use all the features and put your finished product on DVD for others to enjoy. Make home movies 21st century style, complete with special effects, themes, backgrounds, and other elements you can add yourself when you know how to use iMovie and iDVD. This fun and friendly guide makes it easy!"--Resource description page
Print version record
Keywords: iMovie; iDVD; Digital video -- Handbooks, manuals, etc -- Editing; Digital video -- Handbooks, manuals, etc; IMovie; IDVD; Vidéo numérique; Montage; Guides, manuels, etc; Vidéo numérique; Guides, manuels, etc; PHOTOGRAPHY; Techniques; Cinematography & Videography; ART; Film & Video; Digital video; Editing; Handbooks, manuals, etc; Digital video; Handbooks, manuals, etc; Digital video; Digital video; Editing; handbooks; Handbooks and manuals; Guides et manuels